Pengaruh Pengembangan dan Pelatihan Sumber Daya Manusia Terhadap Kinerja Pegawai Dinas PMPTSP Kabupaten Deli Serdang dengan Sharing Session Sebagai Variabel Intervening - Fadhila Putri, Sahira; Darmilisani , Darmilisani; Malikhah, Ikhah (Universitas Muhammadiyah Sorong, 2024)
In the era of globalization, business competition is intensifying, requiring professional human resource management for business sustainability. Training and development of human resources (HR) have become essential strategies to enhance company performance. This study employs the Partial Least Squares Structural Equation Modeling (SmartPLS SEM) method to examine relationships among variables such as customer satisfaction, product quality, and customer loyalty. Data were collected through a questionnaire survey using the Slovin's formula for sampling technique. The analysis results indicate that HR development has a positive and significant impact on employee performance. However, HR training shows no significant effect and even negatively correlates with performance. HR development also positively influences the frequency and quality of sharing sessions among employees, while HR training positively influences participation in sharing sessions. Although sharing sessions positively impacts performance, this relationship is not statistically significant. The sharing session variable does not act as a mediator between HR development or HR training and employee performance.